A persuasão na propaganda de cervejas: sob o enfoque sistêmico-funcional - Silva, Samuel da (2012)
In my studies of linguistics, when dealing with persuasive language, it occurred to me to approach a subject that has interested me for some time. How would the advertisement of beer in Brazil be, in a world where there is clear competition between many companies? Even the manufacturers assume that there is some standardization in the ads. Xavier says, "abroad, beer campaigns resort to humor wisely." Morici, marketing director of FEMSA owner of the brands Kaiser, Sol and Xingu, says that if the ads closely resembled each other in the eyes of consumers, now there is a clear movement to change it. " The efficiency of communication occurs by causing impact and we are all looking forward to it," he says. In this context, it is known that Skol, in 2011, won the Top of Mind award for the tenth time. However the Petrópolis brewery which owns the Itaipava brand, reached second place in the Brazilian beer market, according to latest data from Nielsen research institute in September. What differentiates them from other brands? What would be the reason for this setting in memory of the people? There are several ways to analyze an advertisement. But some features are evident in its preparation. It is primarily of an interactional situation between advertising and reader, with strong support in the use of implicit methods of persuasion, as advertising today is addressed to a community already tired of being overrun by outdated resources of persuasion. According to Fuertes-Olivera et al (2001), advertising seems best represented as a continuum of text functions fluctuating between "information" and "manipulation," according to the idea that advertising is an example of covert communication because it provides the possibility for the authors to avoid responsibility for their statements. Examining these means, I will focus on the enacted roles and projected roles (THOMPSON; THETELA, 1995), the tokens of Attitude (Martin, 2000), the AIDA formula (Unger, 2004), the visual image (MACKEN-HORARIK, 2004) , which contribute to the creation of "textual world" (Downing, 2003). The objective of this research is the critical examination of beer advertisements, analyzing both brands: Skol and Itaipava, to see how persuasuin in such genre occurs. For this we must answer the following research questions: (a) How is a "textual world" in advertising discourse created ? (b) what factors contribute to making this "world" favoring persuasion? and (c) how does the verbal-visual relation in advertising occur?